2019
DOI: 10.1007/s10461-019-02516-6
|View full text |Cite
|
Sign up to set email alerts
|

Alone But Supported: A Qualitative Study of an HIV Self-testing App in an Observational Cohort Study in South Africa

Abstract: HIV self-testing has the potential to improve test access and uptake, but concerns remain regarding counselling and support during and after HIV self-testing. We investigated an oral HIV self-testing strategy together with a mobile phone/tablet application to see if and how it provided counselling and support, and how it might impact test access. This ethnographic study was nested within an ongoing observational cohort study in Cape Town, South Africa. Qualitative data was collected from study participants and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Videoconferencing and telephone consultations involved a ‘respatialisation’ of the clinical encounter (Andreassen et al, 2018). In this way, our participants elaborated how they had to ‘negotiate space’ (comparable to findings of Janssen et al, 2020) to avoid risk of disclosure in synchronous tele‐interactions. A 41‐year‐old patient described how he experienced a call on his phone as more spatially sensitive than receiving and managing information within the app:…”
Section: Resultssupporting
confidence: 66%
“…Videoconferencing and telephone consultations involved a ‘respatialisation’ of the clinical encounter (Andreassen et al, 2018). In this way, our participants elaborated how they had to ‘negotiate space’ (comparable to findings of Janssen et al, 2020) to avoid risk of disclosure in synchronous tele‐interactions. A 41‐year‐old patient described how he experienced a call on his phone as more spatially sensitive than receiving and managing information within the app:…”
Section: Resultssupporting
confidence: 66%
“…Exploration of choice of strategy and venue in the context of this study has been examined in great detail in related recently published qualitative research from this project. 38 39 …”
Section: Discussionmentioning
confidence: 99%
“…These include telephone hotlines, short message service interventions, internet-based platforms and mobile applications (apps). 16,17,18,19,20 A Brazilian study conducted in 2019 showed that an internet-based intervention targeting men who have sex with men led to 21.4% of online participants self-reporting, whilst an interactive voice response telephone line in South Africa was found to link 9.8% of participants to care. 21 Whilst these platforms have shown varied success, the introduction of mHealth interventions for linkage to care and M&E are in line with the South African National Department of Health mHealth Strategy (2015), and should be explored further.…”
Section: Introductionmentioning
confidence: 99%
“…24 The app interface also provides developers with a malleable platform that can be tailored to individual users, allowing them to curate a collection of HIVST information, resources and guidance for testers, whilst also capturing the HIVST result data. 19,20 Recently, HIVSmart TM , a Canadian app, was developed to guide users through the testing process, link them to care, and store the HIVST result data. Preliminary evaluations in key Canadian populations, as well as healthcare workers in South Africa have shown the app to be feasible and acceptable; however, neither HIVSmart TM , nor any other app, has been developed or tested for the general population in LMICs.…”
Section: Introductionmentioning
confidence: 99%